(untitled) (Research, Society and Development, 2021)
This paper presents, initially, a general approach to the basics aspects concerning 13.467/2017 Llw, as known as the Labor Reform, aiming an exposure of key issues about it and also, still in this same thematic, the demonstration of the legislative contradiction between the succinct changes intended by the bill that gave rise to the 13.467/2017 law and the true and countless changes performed by the Laboral Reform, culminating in many impacts on the material and procedural law. In a contextual way, this work exposes, besides, the huge incidence of the constitutional rights on the labor law reality, focusing, primarily on the definition and valuable application of the constitutional principles of the broad access to justice and free and full juridic assistance among the labor law. On a specific theme, this article presents the new 791-A CLT article and explains the serious consequences provoked by this legal device over the labor procedural paradigm, culminating on the undue and harmful mitigation of the constitutional guarantees that were a sign of security and legal protection to the jurisdiction.